Sustainability and challenge-based learning in higher education (Journal of Management and Business Education, 2023)
The main aim of this article is to present a guide for integrating sustainability into university degrees with the use of Challenge-Based Learning (CBL) methodology. In order to achieve this aim, the article starts with a review of the literature on the concept of education for sustainability and the key competences required for its achievement. Secondly, we consider the need to understand the institutional context and the characteristics of the learners before designing the teaching choreography. Thirdly, in order to apply CBL in a structured approach, two models are selected and their complementarity is presented. On that basis, a guide or itinerary is devised showing the steps to be followed in order to include sustainability in the degrees using the methodology selected. This guide has been previously applied and checked at the Faculty of Economics and Business of the University of the Basque Country UPV/EHU. Finally, the difficulties encountered in its application and some questions to be further investigated are raised, due to the scarce existing experiences in the area of social sciences.
Keywords: 2030 Agenda; Challenge-Based Learning (CBL); competences; higher education; sustainability